A dryland re‐vegetation in northern China: Success or failure? Quick transitions or long lags?. Issue 4 (5th April 2019) - Chen, Ning; Ratajczak, Zak; Yu, Kailiang
Abstract: Intensified anthropogenic activities have drastically altered many ecosystems, motivating the use of restoration to regain key ecosystem functions and services and to stem biodiversity losses. Restoration is particularly difficult when human activities have pushed an area into a new state with self‐reinforcing feedbacks. This study investigated a long‐term restoration project in a dryland ecosystem of the Tengger Desert in northwestern China, initiated in 1956. We analyzed shrub and grass cover for 49 yr after the installation of restoration infrastructure that altered external conditions (i.e., using packed straw to reduce wind erosion) and system state (by planting shrubs). After 37–40 yr, the re‐vegetation project was successful in restoring the system to a state similar to native vegetation, with high grass cover (30–50%), low shrub cover (8–10%), and a thick biological soil crust (biocrust). However, the shift to high grass cover did not begin until year 37, before which shrub cover was high (15–20%) and grasses were subdominant (usually <10%). The shift from shrub to grass dominance was abrupt, registering significant nonlinear changes over time and relative to a key driver of vegetation dynamics, estimated biocrust thickness. Biocrust thickness increased gradually over time, which reduced rainfall infiltration into deep soil and thus increased soil moisture available for the shallow‐rooted grasses. The shift from the bare soil state to the steppe state exhibited a long time lag, suggesting that it can take decades to determine whether dryland restoration efforts succeed. The results indicate that persistence might be critical to forcing desired state transitions and that dryland restoration can proceed as a series of time lags, punctuated by abrupt changes in ecosystem state.